Interrelação entre exposição à agrotóxicos e intenção suicida em trabalhadores rurais - Barbosa Junior, Moisés (2024)
Agricultural work is known worldwide as one of the most dangerous professions among the working classes. This fact is caused, for example, by exposure to chemicals. This exposure leads to mental disorders, which cause anxiety and depression and, in more serious cases, lead to suicide. Therefore, this thesis aims to identify the interrelationships between exposure to pesticides and suicidal intention in rural workers through statistical testing. For this, tests were carried out to determine cholinesterase levels in the blood, which identifies exposure to pesticides, and a questionnaire (Self Reporting Questionnaire, SQR-20) was applied to identify suicidal intention in an exposed and an unexposed group. In total, there were 43 respondents, 17 unexposed and 26 exposed. The statistical tests used were the Shapiro-Wilk to analyze the normality of the data, the t-test to identify differences between the study groups in relation to exposure to pesticides and suicidal ideation, multiple logistic regression to identify the predictive variables and the Fisher's exact test was to evaluate the association between the presence/absence of suicidal ideation with exposure to pesticides, sex, alcohol consumption, smoking, marital status and education. The results showed that there are significant differences in relation to the level of cholinesterase in rural workers who have suicidal ideation compared to those who do not. Predictor variables such as gender, education and age do not influence suicidal ideation. The work was completed and achieved the objectives outlined and presents limitations such as the small sample size, which allows further research with larger samples.